2016
DOI: 10.4103/0973-1296.176107
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress-induced apoptotic pathway and mitochondrial dysregulation in HeLa cells treated with dichloromethane extract of Dillenia suffruticosa

Abstract: Ethyl acetate and dichloromethane extract of Dillenia suffruticosa (EADS and DCMDS, respectively) can be a potential anticancer agent. The effects of EADS and DCMDS on the growth of HeLa cervical cancer cells and the expression of apoptotic-related proteins had been investigated in vitro. Cytotoxicity of the extracts toward the cells was determined by 5-diphenyltetrazolium bromide assay, the effects on cell cycle progression and the mode of cell death were analyzed by flow cytometry technique, while the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…Overexpression of GADD153 has been shown to downregulate the antiapoptotic protein Bcl-2 and proapoptotic proteins (such as DR5, GADD34, Trb3, Bim, PUMA). [ 20 21 22 ] The present study showed that FKC induced an early expression of GADD153, and this is similar to our previous finding on HCT 116 cells. Thus, this could suggest the possibility that FKC initiate the apoptotic signaling via ER stress.…”
Section: Discussionsupporting
confidence: 92%
“…Overexpression of GADD153 has been shown to downregulate the antiapoptotic protein Bcl-2 and proapoptotic proteins (such as DR5, GADD34, Trb3, Bim, PUMA). [ 20 21 22 ] The present study showed that FKC induced an early expression of GADD153, and this is similar to our previous finding on HCT 116 cells. Thus, this could suggest the possibility that FKC initiate the apoptotic signaling via ER stress.…”
Section: Discussionsupporting
confidence: 92%
“…ER stress has also been linked with mitochondria-mediated apoptosis involving the Bcl-2 family of proteins. During ER stress, calcium released from the ER is taken up by the mitochondria, causing mitochondrial inner membrane depolarization and caspase-8 activation followed by the release of cytochrome c , which activates procaspase-9, which in turn activates caspase-3, DNA fragmentation, and cell death 33 . The increase of CHOP and spliced XBP1 mRNA expression and activation of Bcl2 family of proteins followed by DOE treatment indicates that DOE could induce ER stress in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the leaves also reportedly possess antimicrobial, dengue antivirus, anti-in ammatory and anti-oxidant properties 3,6,11-13,36,37 . Among these pharmacological characteristics, the anti-cancer effects of D. suffruticosa are perhaps the most intriguing and have been reported to be e cacious in breast cancer and ovarian cancer cell-line studies 3,5,[13][14][15][16][17] . In addition to the cancer cell lines, we found that D. suffruticosa extracts are also selectively effective for cholangiocarcinoma, hepatocellular carcinoma, clear cell renal cell carcinoma, gastric cancer, colon cancer and lung cancer, with little toxic effects to normal kidney (HK2) cells and PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…suffruticosa has been leveraged for various pharmacological and ethnobotanical applications in traditional practices 2,6,[11][12][13] . Existing studies have illuminated the cytotoxic effects of D. suffruticosa extracts on breast and ovarian cancer cell lines 5,[13][14][15][16][17] . To bridge these knowledge gaps, this study aims to assemble the genome of D. suffruticosa, identify and understand the biosynthesis of its phytochemicals based on genomic and metabolic pro ling, and test the anti-cancer e cacy of extracts from different organs of D. suffruticosa against multiple cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%